A systematic review examining socioeconomic factors in trials of interventions for men that report weight as an outcome. (21st February 2022) - McDonald, Matthew D.; Hunt, Kate; Sivaramakrishnan, Hamsini; Moullin, Joanna; Avenell, Alison; Kerr, Deborah A.; Birch, Jack M.; Ntoumanis, Nikos; Quested, Eleanor
Summary: Weight management interventions designed specifically for men have become more common, but the extent to which socioeconomic factors are considered in trials of these interventions is unclear. We synthesized study characteristics, methods, and reporting of interventions with a behavioral component for men that report weight as an outcome, to establish the extent to which socioeconomic factors are considered during intervention design, conduct, and reporting. A comprehensive search was conducted on Medline, Embase, PsycINFO, and CENTRAL for studies published from January 2000 to July 2021. Thirty‐six trials were included. Educational attainment ( n = 24) was the most frequently reported socioeconomic characteristic, followed by working status ( n = 14) and area level deprivation ( n = 12). Seven studies did not report any socioeconomic characteristics. Most studies ( n = 20) did not mention the socioeconomic profile of their samples in relation to study strengths or limitations. Few ( n = 4) consulted with men from lower socioeconomic groups during intervention design. One study examined potential differential intervention effects across socioeconomic groups, with most not powered to do so. Recent feasibility trials ( n = 3) targeting specific socioeconomic groups suggest a potential nascent towards a greater consideration of factors related to equity. To best inform public health policy related to health inequalities, greater consideration of socioeconomic factors is required in trials of men's weight management interventions.